SURGICAL CORRECTION OF JUVENILE IDIOPATHIC SCOLIOSIS. OUR PATIENTS’ PERCEPTION OF THEIR QUALITY OF LIFE - Dittmar-Johnson,Herman Michael (2022)
ABSTRACT Objective: To report the results of our patients who underwent scoliosis correction surgery in relation to their quality of life. Introduction: Juvenile idiopathic scoliosis affects between 1 and 3% of the population during puberty. Treatment will be conservative in most cases. The goal of surgical treatment is to improve coronal and sagittal alignment. The SRS 22 questionnaire is a useful tool for assessing quality of life in these patients. Methods: A retrospective study of 22 patients submitted to corrective surgery for juvenile idiopathic scoliosis between October 2017 and January 2020 was conducted. All of them had curves greater than 45 degrees managed through instrumentation and arthrodesis. Post-surgical quality of life was assessed using the SRS 22 questionnaire. Results: The average age of our patients at the time of the intervention was 15.5 years with a predominance of female patients. The application of the SRS 22 questionnaire generated the following mean scores: pain 4.6, function 4.3, self-image 4.41, mental health 4.89, and satisfaction 5.0. Conclusions: The development of surgical techniques has allowed good results to be achieved in the treatment of scoliosis. The evaluation of our patients using the SRS 22 questionnaire reflects a good quality of life in the 5 parameters evaluated. The main limitations of this study were the small sample size and its retrospective nature. Level of Evidence III; Retrospective, longitudinal, descriptive, observational study.